2020
DOI: 10.3892/mmr.2020.11728
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 enhances radiation-induced tumor migration, invasion and stem-like properties of bladder cancer

Abstract: Bladder cancer (BCa) is the most common cancer of the human urinary system, and is associated with poor patient prognosis and a high recurrence rate. Cancer stem cells (CSCs) are the primary cause of tumor recurrence and metastasis, possessing self-renewal properties and resistance to radiation therapy. Our previous studies indicated that phosphorylated signal transduction and transcription activator 3 (STAT3) may be a potential biomarker to predict radiation tolerance and tumor recurrence in patients with BCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, only T24R cells formed tumors after inoculation in our experiments ( Fig. 6 A) [13] . It was found that untreated tumors took a period of 2 weeks (14 days) to reach around 800mm 3 .…”
Section: Resultsmentioning
confidence: 50%
“…However, only T24R cells formed tumors after inoculation in our experiments ( Fig. 6 A) [13] . It was found that untreated tumors took a period of 2 weeks (14 days) to reach around 800mm 3 .…”
Section: Resultsmentioning
confidence: 50%
“…Fractional irradiation enhanced the invasiveness, motility and stem-like characteristics of bladder cancer cells. Responsibility for this effect was assigned to STAT3 which was previously reported to be significantly phosphorylated in irradiated cells [105]. Knockdown of STAT3 brought a loss of tumor formation in immunodeficient mice.…”
Section: Role Of Stat3 In Bladder Cancermentioning
confidence: 97%
“…48 Wang et al demonstrated that STAT3 increases the radiation-driven motility and stem-like features of bladder cancer. 49 Guanylate-binding protein 2 (GBP2) is involved in offering immunity against pathogens and is overexpressed in glioblastoma multiforme (especially in the mesenchymal phenotype) which is associated with poor clinical outcomes. GBP2 was found to increase invasion through STAT3/fibronectin axis.…”
Section: F I G U R Ementioning
confidence: 99%
“…STAT3 and glucocorticoid receptors cooperatively activate the expression signature of basal‐like triple‐negative breast cancer which contributes to the dismal prognosis and combinational use of inhibitors of these two transcription factors resulting in growth‐inhibitory effects in cell lines and patient‐derived organoid models 48 . Wang et al demonstrated that STAT3 increases the radiation‐driven motility and stem‐like features of bladder cancer 49 . Guanylate‐binding protein 2 (GBP2) is involved in offering immunity against pathogens and is overexpressed in glioblastoma multiforme (especially in the mesenchymal phenotype) which is associated with poor clinical outcomes.…”
Section: Stat3 In Oncology: An Overviewmentioning
confidence: 99%